Compact electronically tunable quadrature oscillator using single voltage differencing gain amplifier (VDGA) and all grounded passive elements - Channumsin, Orapin; Tangsrirat, Worapong (My University, 2017)
This work deals with the design of a compact electronically tunable sinusoidal quadrature oscillator. The proposed quadrature oscillator is designed with a single voltage differencing gain amplifier (VDGA) and all the three grounded passive elements. Its oscillation condition and oscillation frequency can be tuned independently by means of the VDGA transconductance gains. The proposed oscillator also provides the explicit quadrature voltage outputs of almost equal magnitude and low active and passive sensitivity figures. The performance of the oscillator has been demonstrated by PSPICE simulations based on TSMC 0.35-μm CMOS technology.
Keywords: Electronically tunable; Quadrature oscillator; Transconductor; Voltage differencing gain amplifier (VDGA); Voltage-mode circuits